Structural and luminescent properties of red-emitting SrGe4O9:Mn4+ phosphors for white light-emitting diodes with high color rendering index - Kim, Seung Jun; Jang, Ho Seong; Unithrattil, Sanjith; Kim, Yoon Hwa; Im, Won Bin (ELSEVIER SCIENCE BV, 2016)
A red-emitting SrGe3.99Mn0.01O9 (SGO:Mn4+) phosphor have been prepared by a solid-state reaction. The structural and optical properties of SGO:Mn4+ phosphors, together with their thermal quenching property have been investigated. The 3d electrons of Mn4+ at octahedral sites of the SGO host showed a crystal field splitting Dq of 2380 cm(-1) and Racah parameters, B and C of 1970 and 860 cm(-1), respectively. Due to the (4)A(2g) -> T-4(1g) and (4)A(2g) -> T-2(2g) transitions, broad photoluminescence excitation bands were observed at the spectral region spanning from ultraviolet to blue light. The transition from E-2(g) to (4)A(2g) results in a sharp emission peak at 655 nm. When the yellow-emitting Y3Al5O12:Ce3+ and red-emitting SGO:Mn4+ phosphors were incorporated into a blue light-emitting diode (LED), the fabricated white LED showed an emission in the natural white light region with an excellent color rendering index of 92 and a color stability against an increase in the forward current. Thus, SGO:Mn4+ can be a potential red emitting phosphor in the fabrication of white LEDs. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: SOLID-SOLUTION PHOSPHORS; BREDIGITE-STRUCTURE; ENERGY-TRANSFER; EFFICIENT; MN4+; TETRAGERMANATE; SUBSTITUTION; EMISSION